1992
DOI: 10.1007/bf00289868
|View full text |Cite
|
Sign up to set email alerts
|

A typology of personal and environmental sexual harassment: Research and policy implications for the 1990s

Abstract: Most of the research conducted on sexual harassment over the last decade and a half has used categories that are neither mutually exclusive nor exhaustive. This has created problems for researchers: it is difficult to compare results from one study to another, harassment types that have scholarly and legal-policy relevance are omitted, and the ability of researchers to inform legal and policy decisions is diminished as a result of these problems. A comprehensive categorization of harassment types that addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 20 publications
(18 reference statements)
6
93
0
3
Order By: Relevance
“…This concept refers to court precedent and psychological research that partially determines the realm of sexual harassment by determining what is and is not harassment based on what a normal, 'reasonable' woman would find to be either innocuous or offensive. Clearly this is a contentious issue which goes beyond the scope of this paper; but, for our purposes we must remember that our current understanding of sexual harassment must take into account both societal norms and individual perceptions of harassment (see Gruber, 1992;Gruber, Smith, Kauppinen-Toropainen, & Stockdale, 1996;Fitzgerald, Swan & Magley, 1997).…”
Section: Behavioral Aspects Of Sexual Harassmentmentioning
confidence: 97%
“…This concept refers to court precedent and psychological research that partially determines the realm of sexual harassment by determining what is and is not harassment based on what a normal, 'reasonable' woman would find to be either innocuous or offensive. Clearly this is a contentious issue which goes beyond the scope of this paper; but, for our purposes we must remember that our current understanding of sexual harassment must take into account both societal norms and individual perceptions of harassment (see Gruber, 1992;Gruber, Smith, Kauppinen-Toropainen, & Stockdale, 1996;Fitzgerald, Swan & Magley, 1997).…”
Section: Behavioral Aspects Of Sexual Harassmentmentioning
confidence: 97%
“…Indeed, it has been proposed that gender harassment is an expression of male hostility toward women as an outgroup (Pryor & Whalen, 1997) and its greater prevalence within traditionally masculine occupations, such as the military (e.g., Bastian, Lancaster, & Reyst, 1996) and police (e.g., Martin, 1990), may be due to the desire of certain men to assert their authority and keep women in subordinate positions (Gruber, 1992;Gruber & Bjorn, 1982). In fact, experimental research employing the computer harassment paradigm (DallÕAra & Maass, 1999;Galdi et al, 2013;Maass et al, 2003;Siebler, Sabelus, & Bohner, 2008) …”
Section: Hostile Motivesmentioning
confidence: 99%
“…There is no general agreement on what the categories of sexual harassment behaviors should be--they differ from survey to survey (Gruber, 1990;Fitzgerald, 1990). Furthermore, there is often widespread disagreement that all or some of the behaviors falling within a category constitute sexual harassment.…”
Section: Survey Methodsology Discussionmentioning
confidence: 99%
“…Reviews of the sexual harassment literature indicate that there is no single accepted definition of sexual harassment and no generally agreed upon method of assessing and calculating sexual harassment rates (Culbertson & Rosenfeld, 1993;Fitzgerald, 1990;Gruber, 1990Gruber, , 1992Terpstra & Baker, 1991). Gruber's (1992) review of sexual harassment surveys reported rates of 33-69% in the general population, 42-59% in the public sector, 36-75% in the private sector and 28-37% in the academic sector.…”
Section: Survey Methodsology Discussionmentioning
confidence: 99%
See 1 more Smart Citation